Analisis Analisis Strategi Implementasi Integrated Marketing Communication Di PT BPW Shafira Lintas Semesta - Lestari, Mita Dwi; Surianto, Moh Agung (Jurnal Mahasiswa Manajemen, 2023)
Background – The use of integrated marketing communication strategies has become increasingly important in today's business world to achieve consistent and effective communication goals. PT. BPW Shafira Lintas Semesta conducted this research to analyze the implementation strategy of integrated marketing communication they utilize. In the complex business environment, understanding how various marketing elements interact with each other can be a key to success. Aim – The objective of this research is to analyze the implementation strategy of integrated marketing communication conducted by PT. BPW Shafira Lintas Semesta. This study aims to gain insights into how the company combines various elements of marketing communication in their efforts to achieve their business goals. Design / Methodology / Approach – This research employs a qualitative approach, collecting data through interviews and observations at PT. BPW Shafira Lintas Semesta. The collected data is then analyzed using the Miles and Huberman interactive analysis model. The qualitative approach is used to gain in-depth understanding of the integrated marketing communication strategy implemented by the company. Findings – The results of this research indicate that PT. BPW Shafira Lintas Semesta employs an integrated marketing communication model involving various elements such as advertising, sales promotion, events and experiences, public relations and publicity, online marketing and social media, direct and data-based marketing, as well as personal selling. This integrated approach provides insights into how the company coordinates various communication aspects to achieve their marketing goals. Research Implications – The findings of this research could have significant implications for other companies looking to adopt integrated marketing strategies. This study can provide insights into how to organize and manage various marketing elements to mutually support each other and generate a greater impact. Limitations – This research has several limitations, such as its focus on only one company (PT. BPW Shafira Lintas Semesta) and the use of qualitative methods that may not allow for broad generalizations. Additionally, the study is constrained by time and resource availability.